Histopathological Evidence of Lymph Node Metastasis in Papillary Thyroid Carcinoma - GÜLER, BERIL; Can, Nuray; Tastekin, Ebru; Ozyilmaz, Filiz; Sezer, Yavuz Atakan; Guldiken, Sibel; Sut, Necdet; Sarikas, Nurtac; Puyan, Fulya Oz; GÜLER, BERİL; Ayturk, Semra; Celik, Mehmet (My University, 2015)
Prophylactic lymph node dissection is still controversial due to the potentially surgery-related morbidity in management of papillary thyroid carcinomas. So, some histopathological predictors for lymph node metastasis in thyroidectomy specimens may reveal importance. The objective of this study was to define histomorphological indicators of lymph node metastasis in the patients who had been performed thyroidectomy without lymph node dissection. Clinicopathological features of patients archived in Department of Pathology at Trakya University Medical Faculty were reviewed. A total of 211 patients who had been diagnosed as papillary carcinoma and had been performed total thyroidectomy/lobectomy with central/cervical lymph node dissection were included in the study. Clinical features (age, gender, preoperative/postoperative clinical, and laboratory findings) and histopathological features (histological variant, tumor size, focality, extrathyroidal extension, tumor border, lateral tubular growth, intraglandular dissemination, stromal and lymphocytic tumor response, lymphocytic thyroiditis, lymphovascular invasion, lymph node metastasis, number of metastatic lymph nodes, extranodal extension, size of the metastatic foci) were evaluated. Male gender, conventional variant, tumor size greater than 10 mm, multifocality, extrathyroidal extension, lateral tubular growth, intraglandular dissemination, lymphocytic and stromal tumor response, and absence of lymphocytic thyroiditis were predictive, and older age (>= 45 years) and follicular variant PTC were protective for lymph node metastasis. In order to optimize the management of papillary thyroid carcinomas, pathologists should search for the clues of lymph node metastasis particularly intraglandular dissemination, lateral tubular growth, tumor border and lymphocytic/stromal tumor response, multifocality, concomitant lymphocytic thyroiditis besides the actual prognostic criteria especially in younger aged male patients.